A non-abelian Hom-Leibniz tensor product and applications - Mirás, José Manuel Casas (2017)
The notion of non-abelian Hom–Leibniz tensor product is introduced and some properties are established. This tensor product is used in the description of the universal (α-)central extensions of Hom–Leibniz algebras. We also give its application to the Hochschild homology of Hom-associative algebras.